ISOLASI DAN IDENTIFIKASI MIKROBA PADA SAMPEL MINUMAN YOGHURT DRINK DI ALUN-ALUN SITUBONDO - Rahman, Ahmad Taufikur; Elhany, Nurul Avidhah; Fajar, Muhammad Thoifur Ibnu (PRIMA EKSAKTA, 2025)
Food is everything that comes from biological sources and water, both processed and unprocessed, which is intended as food or drink for human consumption. In addition to being nutritious, food must also be free from hazardous materials in the form of chemical contaminants, pathogenic microbes and other materials. Microbes can contaminate food through water, dust, air, soil, food processing equipment and secretions from the intestines of humans or animals. Yoghurt is the result of milk fermentation with the help of lactic acid bacteria. This product is widely found in the community because of the benefits and nutrients contained in it. To find out the microbial content, both beneficial and not, microbiological tests must be carried out on yogurt drink samples that are sold freely in the community. Bacterial isolation is carried out by the pour cup method on MRSA media. Bacterial isolation is carried out by diluting the yogurt sample to a dilution of 10-6. The sample was then poured 1 ml into a Petri dish containing MRSA media. Then incubation was carried out for 48 hours at a temperature of 360C. The results of bacterial isolation were then counted and identified by observing the morphology of bacterial colonies that grew on MRSA media then continued with the gram staining test and observation of microscopic characteristics using a microscope. In addition, motility and biochemical tests of bacteria were also carried out (catalase test, citrate test, nitrate test, H2S test, MR test, VP test, starch hydrolysis test, Urea test and He test). The results of microbial identification in yogurt drink samples in Situbondo square are Streptococcus thermophilus and Lactobacillus sp. Both of these bacteria are lactic acid bacteria that play a role in the fermentation process and are not pathogenic to humans.